2009
DOI: 10.1111/j.1745-6584.2009.00594.x
|View full text |Cite
|
Sign up to set email alerts
|

Variable‐Density Flow and Transport Simulation of Wellbore Brine Displacement

Abstract: Borehole dilution tests have been used for characterization of aquifer hydrogeologic properties for several decades. Based on the principles of borehole dilution tests, we conducted what more appropriately may be considered a wellbore fluid displacement test in a limestone aquifer in South Carolina. Our study area is a quarry in the coastal plain of South Carolina. Using a solution of reagent grade NaCl and deionized H(2)O as a tracer, a brine slug was introduced into a 5 cm (2 in.) diameter Schedule 40 PVC we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…In addition to the Toolbox approach, chemical tracers have been used in characterizing fracture flow conditions. Tracer methods include single point dilutions (Hall 1993), ambient flow tracer studies (Pitrak et al 2007;Shafer et al 2010;Maurice et al 2011), single borehole pumping and profiling tests (Tsang et al 1990;Brainerd and Robbins 2004), and multi-well pumping tests (Marine 1980;Novakowski et al 2004;West and Odling 2007). Difficulties associated with tracer behavior have been presented in numerous studies (Feuerstein and Selleck 1963;Smart and Laidlaw 1977;Shiau et al 1993;Magal et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the Toolbox approach, chemical tracers have been used in characterizing fracture flow conditions. Tracer methods include single point dilutions (Hall 1993), ambient flow tracer studies (Pitrak et al 2007;Shafer et al 2010;Maurice et al 2011), single borehole pumping and profiling tests (Tsang et al 1990;Brainerd and Robbins 2004), and multi-well pumping tests (Marine 1980;Novakowski et al 2004;West and Odling 2007). Difficulties associated with tracer behavior have been presented in numerous studies (Feuerstein and Selleck 1963;Smart and Laidlaw 1977;Shiau et al 1993;Magal et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to fluorescent dyes, the use of NaCl requires larger amounts, which is why density has to be considered. Shafer et al (2010) observed density effects during their test, but attained mean concentrations of more than 20 g/L after mixing. Lamontagne et al (2002) conducted several tests and found no density-driven movement while using low concentrations.…”
Section: Hosepipe Methodsmentioning
confidence: 93%
“…For this and also for a detailed investigation of a particular depth, point injections need to be used (Maurice et al 2011). Both uniform and point injections can be conducted using different techniques and injection devices, for example hosepipes or funnels, as well as different tracers, and with or without the use of pumps in the injection well or a GMW nearby (Palmer 1993;Shafer et al 2010;Maurice et al 2011). Packers can be used to separate defined segments of a borehole for detailed investigation, which, however, may cut off vertical flow (Drost et al 1968;Grisak et al 1977;Lamontagne et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these methods there are several different types of tracerrelated tests that are currently used for characterization. Some include single borehole point dilutions (Hall 1993), tracer tests under natural flow conditions (Pitrak et al 2007;Shafer et al 2010), or tests under pumping conditions between one or more wells (Novakowski et al 2004;West and Odling 2007). Tracer tests can also be used to determine the connectivity between wells (Marine 1980;Tsang et al 1990).…”
Section: Introductionmentioning
confidence: 99%